Specific sequence of Plasmodium falciparum DBL domains associated with severe malaria outcome - Sulistyaningsih, Erma; Fitri, Loeki Enggar; Loescher, Thomas; Berens-Riha, Nicole (UNEJ e-Proceeding, 2014)
Duffy-binding like (DBL) domains of Plasmodium falciparum are believed to be involved in erythrocytes invasion and infected erythrocytes cytoadhesion during the blood stage of malaria infection. In Plasmodium falciparum, DBL domains found in the two different protein families; Erythrocyte Binding Ligand (EBL) including EBA-175, EBA-140, EBA-181 and EBL-1, and Plasmodium falciparum Erythrocyte Membrane Protein-1. The study aimed at investigating the specific sequence of Plasmodium falciparum involved in severe malaria outcome.Blood samples from severe and uncomplicated falciparum malaria cases from Papua and South Kalimantan province, Indonesia, were collected for DNA extraction. A dried blood on filter paper were used for RNA extraction. PCR was performed using UNIEBP primers and directly sequenced. Internal var D primers were designed according to the sequencing of the ~550 bp band produced by UNIEBP primers. The nucleotide sequences were analyzed by NCBI BLAST. Multiple bands ranging from nearly 250 bp to 1 kb were resulted from gDNA in all samples. Two isolates yielded bands of 450 and 525 bp, three isolates showed three bands additionally 250 bp, one isolate presented four bands additionally 800 bp and one isolate resulted one band additionally 1 kb.Amplification of cDNA from severe malaria cases produced one to four bands ranging from 250 bp to 700 bp, and no band observed from cDNA of uncomplicated malaria. Sequencing of the 418 bp bands matched with the eba-175 gene, the 316 bp determined as DBL1a domain and 486 bp band matched with the DBLg domain isolated from placenta of PAMâs Malawian woman. The expression of a 237 bp sequence corresponding to var D gene, was detected solely in severe malaria patients, implicating an association of gene expression and manifestation of severe malaria. Further characterization of the var D gene with a larger sample size is required to draw a definite conclusion. Keywords: DBL domains, Plasmodium falciparum, severe malaria, var D gene.